Main factors cointribuiting to nursing students’ low academic performance - Alonso Trujillo, Javier; Rosete Villegas, Cristian Uriel; Alonso Ricardez, Abraham (CuidArte Journal, 2018)
Nursing students’ low academic performance has been the subject of various studies and has become a challenge for schools. Several possible reasons for this low performance are put forward in the literature. This study applies an algorithm based on the decision tree theory, which reveals the main factors contributing to low academic performance, the model’s efficiency, and the prediction error. Methodology: Observational, prospective, analytical, and predictive cross-study. The study’s design includes the observation of the following predictive variables: formal work activity, unfavorable socioeconomic level, lack of physical activity, commute greater than 1 hour, unfavorable family context, free time greater than 28 hours per week, high level of stress, signs of anxiety, and signs of depression. The variable to predict is low academic performance. Results: The main factors predicting low academic performance are, in order of importance, formal work activity, unfavorable socioeconomic level, and high level of stress. Conclusions: Formal work activity, unfavorable socioeconomic conditions, and emotional problems lead to low academic performance in nursing students.